The nuclear transcription factor ZmCCT positively regulates salt and low nitrogen stress response in Maize - Yanbing Zhang; Zhihuan Zhou; Senlin Xiao; Yipu Li; Suxiao Hao; Fan Que; Zhongjia Liu; Liyu Shi; Yingying Shi; Zhaoheng Zhang; Yang Xu; Tonghui Li; et al. (Plant Stress)
Abiotic stresses such as drought, salinity, and low nitrogen negatively affect maize growth and development, leading to significant yield reductions. In previous studies, we successfully cloned the maize transcription factor gene ZmCCT and demonstrated its role in flowering regulation through the photocycle pathway. Additionally, we found that transposable element (TE) insertions in the ZmCCT promoter region reduce maize resistance to stem rot. However, although ZmCCT was cloned years ago, its key molecular mechanisms in response to biotic and abiotic stresses remain unclear. In this study, we demonstrated that ZmCCT plays important roles in salt and low-nitrogen stress tolerance in maize, using the Y331/Y331-ΔTE inbred line and 83B28H1/H1/83B28H5/H5 haplotypes. Through DAB staining and H2O2 content analysis, we confirmed that Y331-ΔTE and 83B28H5/H5 exhibited less membrane system damage and greater stress tolerance following high-salt and low-nitrogen treatments. Under high salt and low nitrogen stress conditions, the Y331-ΔTE and 83B28H5/H5 inbred lines demonstrated superior phenotypic performance compared to the Y331 and 83B28H1/H1 lines. Furthermore, transgenic Arabidopsis thaliana overexpressing ZmCCT showed enhanced tolerance to salt and low nitrogen stress compared with wild-type plants. In addition, RNA-Seq analysis indicated that ZmCCT can directly activate these salt inducible genes of ZmNADP, ZmPP2C, ZmbHLH55, ZmPIP1–1, ZmPIP2–4 and some low nitrogen involved genes of ZmWRKY47, ZmMYB44, ZmMYB36, ZmPIN10 and ZmbHLH83 when respond to high salt and low nitrogen tolerance. Taken together, our results have provided that ZmCCT functions as important roles in high salt and low nitrogen stress tolerance and further highlight that ZmCCT has multiple abiotic stress roles. These results indicate that ZmCCT may be a potential candidate to enhance plant salt and low nitrogen stresses in mazie molecular design breeding.